2008
DOI: 10.1063/1.2894518
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric properties of BixCo2−xMnO4 (⩽x⩽0.3)

Abstract: We present the structural, dielectric and magnetization study of single phase polycrystalline Bi x Co 2−x MnO 4 ͑0 ഛ x ഛ 0.3͒, synthesized by a conventional solid state route. All the samples have the cubic spinel structure with Fd3m space group. Bi-substitution in Co 2 MnO 4 stabilizes the ferroelectric transition at a temperature of ϳ350 K and enhances the dielectric constant with a relaxor behavior. The capacitance-voltage ͑C-V͒ measurements confirm the ferroelectric nature at room temperature. Ferrimagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 22 publications
1
33
0
1
Order By: Relevance
“…BiMnO 3 exhibits ferroelectric as well as ferromagnetic properties and hence can be used as a good multiferroic material [10,11]. The Bi doped manganites have been shown to be prospective materials for multiferroic and bolometric applications [12][13][14][15]. Bi 0.5 Sr 0.5 MnO 3 has been shown to be a promising candidate for use as a cathode material in solid oxide fuel cells because of its high electrochemical performance [16].…”
Section: Introductionmentioning
confidence: 99%
“…BiMnO 3 exhibits ferroelectric as well as ferromagnetic properties and hence can be used as a good multiferroic material [10,11]. The Bi doped manganites have been shown to be prospective materials for multiferroic and bolometric applications [12][13][14][15]. Bi 0.5 Sr 0.5 MnO 3 has been shown to be a promising candidate for use as a cathode material in solid oxide fuel cells because of its high electrochemical performance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Details of the material synthesization are given elsewhere. 4 The crystal structure of the materials was studied at room temperature using a Bruker D8 x-ray diffractometer with Cu K␣ radiation in 2 range of 15°-75°. The dc-conductivity measurements were performed using the standard four-probe technique in a temperature range of 150-400 K. The temperature was controlled within Ϯ50 mK using a Lakeshore temperature controller.…”
Section: Methodsmentioning
confidence: 99%
“…11 We propose to engineer a class of materials by incorporation of Bi in the spinel structure of cobalt manganite spinels ͑Co 2 MnO 4 ͒. In our earlier work 4 we have shown that BixCo 2−x MnO 4 ͑Ͻ0x Ͻ 0.3͒ exhibit a strong magnetoelectric coupling up to ϳ180 K. We present here the detailed structural and electrical properties of the Bi x Co 2−x MnO 4 ͑0.0Յ x Յ 0.3͒ system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, coexistence of FE and FM is achieved through induction of non-magnetic ions having stereochemically active lone pair of electrons, which can introduce off centering in the structure containing magnetic transition metal oxides [5,6]. Recently, we have reported that incorporation of Bi has introduced noncentrosymmetric charge ordering and consequently polarization in the Co 2 MnO 4 spinel structure along with non-collinear antiferromagnetic (AFM) ordering among the Co 2 + sublattices, which lead to FM and magnetoelectric effect [7,8]. It is important to mention here that the above work was reported for the bulk material, whereas these properties in the thin film form are required for device realization.…”
Section: Introductionmentioning
confidence: 98%